DIFFERENT POINTS OF VIEW TO THE STUDY OF CONVERSION - Khaydarova Nigora; Aripova Rayyona (TADQIQOTLAR, 2025)
Annotation:  This  article  presents  an  overview  of  the  different  theoretical approaches to the study of conversion, focusing on morphological, syntactic, semantic, and cognitive perspectives. Special attention is given to the debates on the status of conversion as a distinct type of word-formation, its classification, and the mechanisms behind it.